Operational Improvement in Infrastructure Department Contract Service Performance in Coal Mining Company - Ruth Sagala; Nur Budi Mulyono (Journal of International Conference Proceedings, 2021)
Infrastructure is defined as the physical facilities that provide the primary support for carrying out an organizational business process. Infrastructure includes all technical aspects and facilities required to keep an organization's operations or business processes running smoothly. Infrastructure facilities are considered to all facilities related to an office building, road, water treatment plant, water distribution, airport, building and office, drainage, reservoir, bunding, retaining wall, bridge, sewerage treatment plant, power distribution, power plant, telecommunication, fuel facilities, fuel distribution, housing, port and jetty, and other facilities that support the operational activities of an organization's business process. PT. Kaltim Prima Coal considers the service level in maintenance activities that are related to the compliance performance in quality service, lead time, and work completion performance. These are some of the performance indicators used to measure the Infrastructure Department's agreement for contract maintenance. An operational strategy improvement in infrastructure department contract service maintenance is expected to improve the service level, shorten the lead time and increase customer satisfaction in order to meet the performance indicators. Six-Sigma – DMAIC (Define-Measure-Analyze-Improve-Control) approach is implemented to overcome the service level compliance problem in infrastructure operational maintenance service. Six Sigma has proven to be effective in reducing quality defects, eliminating variation, and significantly increasing the organization performance. The major issue will be investigated using fish bone analysis to determine the root cause and optimize the operational maintenance activities and increase the service level performance from 84 percent average to 100 percent.